Newly discovered Neanderthal remains from Shanidar Cave, Iraqi Kurdistan, and their attribution to Shanidar 5. Issue 111 (October 2017) - Pomeroy, Emma; Mirazón Lahr, Marta; Crivellaro, Federica; Farr, Lucy; Reynolds, Tim; Hunt, Chris O.; Barker, Graeme
Abstract: The Neanderthal remains from Shanidar Cave, excavated between 1951 and 1960, have played a central role in debates concerning diverse aspects of Neanderthal morphology and behavior. In 2015 and 2016, renewed excavations at the site uncovered hominin remains from the immediate area where the partial skeleton of Shanidar 5 was found in 1960. Shanidar 5 was a robust adult male estimated to have been aged over 40 years at the time of death. Comparisons of photographs from the previous and recent excavations indicate that the old and new remains were directly adjacent to one another, while the disturbed arrangement and partial crushing of the new fossils is consistent with descriptions and photographs of the older discoveries. The newly discovered bones include fragments of several vertebrae, a left hamate, part of the proximal left femur, a heavily crushed partial pelvis, and the distal half of the right tibia and fibula and associated talus and navicular. All these elements were previously missing from Shanidar 5, and morphological and metric data are consistent with the new elements belonging to this individual. A newly discovered partial left pubic symphysis indicates an age at death of 40–50 years, also consistent with the age of Shanidar 5 estimated previously. Thus, the combined evidence strongly suggests that the new finds can be attributed to Shanidar 5. Ongoing analyses of associated samples, including for sediment morphology, palynology, and dating, will therefore offer new evidence as to how this individual was deposited in the cave and permit new analyses of the skeleton itself and broader discussion of Neanderthal morphology and variation.